Evaluation of Upper Limb Exercise with Respiratory Muscle Stretch Gymnastics for Lung Function and Quality of Life in Copd Patients - Ulfa Nur Rohmah; Muhammad Amin; Makhfudli Makhfudli (Universitas Jember, 2023)
Progressive decline in pulmonary function can be unveiled by shortness of breath and lower physical ability, and decreased life quality among COPD. This study aimed to investigate the effects of Upper Limb Exercise with Respiratory Muscle Stretch Gymnastics for lung function and quality of life in COPD patients. A quasi-experiment design (pre-post test with control group design). 50 respondents participated, divided into two groups at Airlangga Hospital and Bangil Regency Hospital, Indonesia, with consecutive sampling. Data were collected by a spirometry test for lung function using the COPD Assessment Test (CAT), subsequently was analyzed by employing aired T-test and MANOVA test. Treatments were given three times a week for a month. The outcome showed that the treatment group increased lung function with FEV1 value and quality of life before and after the treatment with a value of 0.000 (p<0.05), but the control group was otherwise. There were lung function and quality of life values with MANOVA of 0.011 (p<0.05). Upper Limb Exercise with Respiratory Muscle Stretch Gymnastics improve lung function and quality of life among COPD patients to complement pharmacological therapy.